PLATELET INDICES IN CORONARY ARTERY DISEASE WITH PRE-DIABETES - TALWAR, DHRUV; KUMAR, SUNIL (International Journal of Psychosocial Rehabilitation, 2020)
One of the most common cause of death world over is Coronary artery disease and it comprises a major public health problem in this decade. Increased platelet agglutination in association with other risk factors increase the proabibility of development of myocardial ischemia. In diabetic patients, the mean platelet volume is increased when comparison was done with subjects who are normal.However, this relationship between Mean plaetelet volume and pre-diabetes is not evakuated properly (1-2).